The place of the family of origin in romantic relationships of adults with intellectual disabilities. - Żyta, Agnieszka (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The family in the lives of people with intellectual disabilities is not only their closest and most essential social group, but often also their basic or even the only source of support in everyday life from childhood to the late old age. In a situation of adults with intellectual disabilities who start a new romantic relationship (of a formal or informal nature), the family of origin may play different roles and occupy different places in their everyday lives. The research using the phenomenographic method of qualitative research on experiences related to being in long-lasting romantic relationships conducted with adults with intellectual disabilities allowed the author to show the place of family members (parents, siblings, extended family) in their everyday lives and in their relationships with partners.